Evaluation of the use of resistant starch in the prevention of colitis caused by the antibiotic tetracycline (Research, Society and Development, 2022)
This study aimed to evaluate the effect of diets with resistant starches in preventing the occurrence and/or severity of pseudomembranous colitis in animals treated with and without the antibiotic tetracycline. The experiment was carried out with 20 female Wistar rats, divided into four groups that received different diets: pregelatinized starch with 9.5% resistant starch; pregelatinized starch with 9.5% resistant starch and tetracycline; pregelatinized starch and resistant starch with 18.1% resistant starch and pregelatinized starch and resistant starch with 18.1% resistant starch and tetracycline. Weight, feed and water consumption were monitored for 21 days and analysis of total cholesterol, triglycerides and liver, muscle and cardiac glycogen were performed. Histological analysis of staining by hematoxylin-eosin and periodic acid Schiff of the animals' large intestine was performed. The results showed changes in the cytoarchitecture of the intestinal colon of the animals, which varied according to the treatment to which they were submitted, showing from mucosal atrophy in animals that received tetracycline, the formation of edema and congestion of vessels in the submucosa in animals fed 18 .1% of resistant starch and the presence of cellular debris in the lumen of the organ and loss of brush border when it was associated with tetracycline, demonstrating changes in the absorption and intestinal functioning of the animals, which contributes to the loss of organ homeostasis.